The Role of Albumin in Human Toxicology of Cobalt: Contribution from a Clinical Case. (31st October 2010) - Catalani, Simona; Leone, Roberto; Rizzetti, Maria Cristina; Padovani, Alessandro; Apostoli, Pietro
Abstract : The distribution and adverse effects, especially to optic and acoustic nerves, of cobalt released from a hip arthroplasty and its association with albumin were studied. The analysis of cobalt was performed in plasma, whole blood, urine, and cerebrospinal fluid by inductively coupled plasma mass spectrometry (ICP-MS). The fraction of albumin binding the metal was determined by colorimetric assay using dithiothreitol (DTT). In all the biological matrices very high levels of cobalt were measured, but contrary to expected, a higher concentration in whole blood than in plasma was observed. The determination of altered albumin confirmed this hypothesis. This evidence might indicate an alteration in the binding of cobalt to albumin and a consequent increase in the concentration of the diffusible (free) fraction of the metal. This appears an interesting starting point for further investigations for identifying and better understanding cobalt neurotoxicity, apparently not so frequent in occupational medicine and clinical practice.